Effect of Preconditioning and Hypothermia in Ischemia–Reperfusion Injury to the Endothelial Cells of Blood Vessels in Oryctolagus cuniculus - Ismet, Mohamad F.; Moenadjat, Yefta; Kekalih, Aria (The New Ropanasuri Journal of Surgery, 2017)
Introduction. Ischemia/reperfusion injury (I/RI) remain a problem in post–hypoxia period, leading to remote organ injury. Studies showed that ischemic preconditioning (IPC) and hypothermia (HI) let destructive effect of ischemia to be minimized. The aim of study was to find out the impacts of interventions such as IPC and HI on morphology and function of the endothelial distal to ligation (ischemia) and contralateral vessel (I/RI). Method. An experimental study carried out by ligation the right common femoral artery of Oryctolagus cuniculus to induce ischemia. Endothelial cells distal to ligation and contralateral side was subjected to investigation. The effect of IPC and HI were investigated and compared to those in I/RI. Results. Morphological study showed significant difference scores between endothelial damage in ipsilateral vessels in interventional subjects with control, and intervention with I/RI group (p 0.05). Conclusion. Ischemia may lead to remote endothelial dysfunction; IPC and HI showed the efficacy to minimize the impact of reperfusion.